Linking soil adsorption-desorption characteristics with grain zinc concentrations and uptake by teff, wheat and maize in different landscape positions in Ethiopia - Desta, Mesfin K.; Broadley, Martin R.; McGrath, Steve P.; Hernandez-Allica, Javier; Hassall, Kirsty L.; Gameda, Samuel; Amede, Tilahun; Haefele, Stephan M. (Frontiers in Agronomy, 2023)
Zinc deficiencies are widespread in many soils, limiting crop growth and contributing to Zn deficiencies in human diets. This study aimed at understanding soil factors influencing grain Zn concentrations and uptake of crops grown in different landscape positions in West Amhara, Ethiopia.On-farm experiments were conducted in three landscape positions, with five farmers' fields as replicates in each landscape position, and at three sites. Available Zn from the soil (Mehlich 3, M3, Zn) and applied fertilizer (NET_FERT Zn, estimated based on adsorption/desorption characteristics and applied Zn) were related to the actual grain Zn concentration and uptake of teff, wheat, and maize. Zinc fertilizer treatments tested were Zn applied at planting (basal), basal plus side dressing and a control with no Zn applied.Zn treatments had a significant effect on grain Zn concentration (increase by up to 10%) but the effect on grain yield was variable. Differences in crop Zn concentrations along the landscape positions were observed but not at all sites and crops. Trial results showed that soils with higher soil pH and Soil Organic Carbon (SOC) (typical of footslope landscape positions) tended to adsorb more applied Zn (reduce NET_FERT Zn) than soils with lower soil pH and SOC (typical of upslope landscape positions). Zn availability indicators (M3, NET_FERT Zn, clay%) explained 14-52% of the observed variation in grain Zn concentrations, whereas macronutrient indicators (Total N, exchangeable K) This is a provisional file, not the final typeset article together with M3 Zn were better in predicting grain Zn uptake (16 to 32% explained variability). Maize had the lowest grain Zn concentrations but the highest grain Zn uptake due to high yields.We found that the sum of indigenous and fertilizer Zn significantly affects grain Zn loadings of cereals and that the associated soil parameters differ between and within landscape positions. Therefore, knowledge of soil properties and crop characteristics helps to understand where agronomic biofortification can be effective.